On Possibilities and Thought Experiments - Batens, Diderik (Rescher Studies. A Collection of Essays on the Philosophical Work of Nicholas Rescher, 2008)
This paper concerns two related recent books by Nicholas Rescher, Imagining Irreality on possibilities and What If? on thought experiments. Apart from an expository part, the present contribution consist on the one hand of some proposed elaborations, especially of two technical points, and on the other hand of some discussion concerning points where I am in doubt about Rescher's precise stand and of some suggestions for further research.